Characteristics of Hate Speech and Freedom of Expression in the Perspective of Maqāṣid Al-Sharī’ah - Agus Purnomo; Umi Sumbulah; Nor Salam; Hikam Hulwanullah (Institut Agama Islam Negeri Batusangkar, 2023)
This article discusses the model of freedom of speech that is prohibited and categorized as hate speech using the maqāṣid al-sharī’ah approach. The prohibition and sanctioning of hate speech has been a dilemma. On the one hand, it prevents someone from hurting other people’s feelings. On the other hand, it violates freedom of speech. This research is a literature study in which the data were obtained from the texts of the Qur’an. Through normative-empirical and maqāṣid al-sharī’ah approaches, this study reveals that freedom of speech is part of human rights, which in the maqāṣid al-sharī’ah perspective can be categorized as protection of freedom of thought (ḥifẓ al-’aql). However, when freedom of speech is not controlled, it can potentially become hate speech that can threaten another maqāṣid al-sharī’ah, namely the protection of the soul (ḥifẓ al-nafs). The identification and categorization of an action as hate speech or an expression of freedom of speech are based on the benefits. The findings of this study are expected to educate the public in distinguishing between freedom of speech and hate speech according to maqāṣid al-sharī’ah to minimize conflict and hostility.